2018
DOI: 10.1902/jop.2017.170105
|View full text |Cite
|
Sign up to set email alerts
|

Effect of topically applied hyaluronic acid on pain and palatal epithelial wound healing: An examiner‐masked, randomized, controlled clinical trial

Abstract: Topical application of hyaluronic-acid exhibits positive impact on post-operative pain, burning sensation and accelerates palatal wound healing in terms of epithelization and color match.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
58
2
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(73 citation statements)
references
References 50 publications
10
58
2
3
Order By: Relevance
“…The authors failed to find significant intergroup differences in plaque levels, bleeding index, presence of inflammation around the suture and presence of granulation tissue . In contrast, beneficial clinical effects were previously reported for HA when topically applied in a gel form in oral surgery as well as periodontal therapy . Some hypotheses can be advanced to explain the lack of effect of HA as observed in this study.…”
Section: Discussioncontrasting
confidence: 64%
“…The authors failed to find significant intergroup differences in plaque levels, bleeding index, presence of inflammation around the suture and presence of granulation tissue . In contrast, beneficial clinical effects were previously reported for HA when topically applied in a gel form in oral surgery as well as periodontal therapy . Some hypotheses can be advanced to explain the lack of effect of HA as observed in this study.…”
Section: Discussioncontrasting
confidence: 64%
“…Both PRF and hyaluronic-acid may provide significant benefits for wound healing parameters and reduce pain. 24,25 In our study, all patients were administered palatal stents. Thus complaints about the donor site (discomfort, pain, bleeding) might have decreased due to a reduction in pressure over the wound, independent of the graft length and thickness.…”
Section: Discussionmentioning
confidence: 99%
“…At day 30 and 90 there was no statistically significant difference between both groups. Yildrim et al 2018 (19) conducted that 0.2% HA showed less pain than the control group on day 7.…”
Section: Discussionmentioning
confidence: 97%
“…(18) HA has an important part in wound healing, it possesses a role in the migration and adherence of polymorph nuclear leucocytes and macrophages at the inflamed site and phagocytosis of invading (1589) microbes, promotes cell proliferation, migration of cells into granulation tissue matrix and granulation tissue organization. (18) Yildrim et al 2018 (19) performed a study that evaluated the effect of two different concentrations (0.2 & 0.8%) of topical HA on post-operative patient discomfort and wound healing of palatal donor sites following FGG. The study concluded a significant complete epithelization and post-operative pain reduction in patients treated with 0.2% HA gel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation